Research into rheological transformations in a piezoceramic ultrasonic sensor of fluid level control - Stencel, Iosiph; Litvinov, Konstantin (Eastern-European Journal of Enterprise Technologies, 2016)
It was established that in the piezoceramic transducers of electric excitation pulse into ultrasonic signal that are used for measuring control of level of fluids and gas volumetric rate, similar electromagnetic processes occur. The effect of change in parameters of piezoceramic element on the formation of ultrasonic pulse was studied. It was shown that to create the pulse, the electric field intensity of this element is converted to electrodynamic force, which causes elastic deformation of a membrane unit. It was shown that the elastic deformation of a membrane unit causes electromotive force, which creates current in a piezoceramic element. The latter causes a secondary electrodynamic force, which is braking for a mechanical unit that leads to the deformation of mechanical ultrasonic oscillations. Physical models of irreversible rheological transformations are given and it is shown that the following processes occur in the piezoceramic transducers: conversion of electric exciting momentum to mechanical motion of a membrane of transducer, the latter to mechanical ultrasonic oscillations, and these oscillations to electromotive force of a piezoceramic element. The processes of irreversible rheological transformations are presented by the integrated pulse Dirac delta function. It was shown that such transformations are described by nonlinear differential equations, the right part of which characterizes the rate of decrease (flow) of electrical or mechanical energy, and these equations are the core of the integrated pulse Dirac delta function. Analytical solution of nonlinear differential equations of transfer of energy, mass and momentum by a zero gradient was obtained. A mechanism of the effect of temperature of heating of a piezoceramic element on the ultrasonic pulse form was determined. The essence of the impact is the fact that as a result of the heating of this element by electric current of excitation pulse and secondary electromotive force, its linear dimensions, resistance and density of the material change, leading to a phase shift of the ultrasonic pulse.